CEO & CFO Education and R&D Investment in Indonesia - Iman Harymawan; Mohammad Nasih; Dian Agustia; Melinda Cahyaning Ratri; John Nowland (Australasian Accounting, Business and Finance Journal, 2020)
This study examines how the research and development (R&D) investments of listed companies in Indonesia are influenced by the educational characteristics of their CEOs and CFOs. This study uses 368 observations from 150 listed companies on the Indonesian Stock Exchange for the period 2010 to 2015. We find that CEOs with higher educational levels invest more in research and development. This is consistent with more education instilling a longer-term perspective on corporate managers. We also find that CFOs with accounting certifications invest less in R&D, consistent with the risk-adverse nature of the accounting profession. For companies and shareholders, our findings indicate the need for a greater understanding of the factors associated with R&D investments in Indonesia and other developing markets. Particularly, factors related to the background experience of CEOs and other executives, whose characteristics can have a real impact on the R&D investment decisions of firms. Our results show that the education of CEOs and CFOs is associated with their investment decisions in research and development. Thus, different education backgrounds create a bias for or against R&D investment in Indonesian firms.
Keywords: CFO; CEO; Education; R& amp; D Investment; Indonesia